2021
DOI: 10.1155/2021/8825698
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of ZiBuPiYin Recipe on db/db Mice via PI3K-Akt Signaling Pathway by Activating Grb2

Abstract: Background. Diabetes-associated cognitive decline (DACD) is one of the nervous system dysfunctions induced by diabetes mellitus with cognitive impairment as the major symptom. In a previous preliminary proteomic study, we found that endoplasmic reticulum processing and PI3K-Akt signaling pathway might be impaired in DACD pathogenesis. In addition, growth factor receptor-bound protein 2 might be a crucial protein as a molecular target of the neuroprotective effects of ZiBuPiYin recipe (ZBPYR). Methods. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…We used SPSS 25.0 (IBM, Armonk, NY) to calculate statistics. When no obvious abnormality was found, Student's t test was used after the comprehensive normality test of D'Agostino and Pearson [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used SPSS 25.0 (IBM, Armonk, NY) to calculate statistics. When no obvious abnormality was found, Student's t test was used after the comprehensive normality test of D'Agostino and Pearson [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-two out of 32 studies tested naturally derived compounds, they include: compounds rich in flavonoids such as yuzu extract ( Yang et al, 2013 ), bee pollen extract ( Liao et al, 2019 ), N. incisum extract ( Jiang et al, 2020 ) and flavonoids of okra fruit ( Yan et al, 2021 ); compounds containing alkaloids, such as Puerariae radix ( Huang et al, 2019 ), ZiBuPiYin ( Ren et al, 2021 ), evodiamine ( Wang et al, 2018 ; Chou and Yang, 2021 ) and Peganum harmala ( Saleh et al, 2021 ); aquesous cinnamon extracts ( Madhavadas and Subramanian, 2017 ), which contain type A linked procyanidin trimer; schisandra chinensis extract ( Yan et al, 2017 ), which contains ligand diabenzo [a, c] cyclooctadiene; sea cucumber cerebrosides ( Li et al, 2019 ), which is a class of neural glycospinolipids; osthole ( Yao et al, 2019 ) which is a derivative of coumarin; curcumin ( SoukhakLari et al, 2018 ), which is the main ingredient of turmeric; litchi chinensis seed fraction ( Sun et al, 2020 ), which entails phenolic compounds and glycosides; Asiatic acid ( Ahmad Rather et al, 2019 ), which is a pentacyclic triterpenoid; Yonkenafil ( Zhu et al, 2019 ), which is a novel phosphodiesterase type 5 inhibitor and an analogue of sildenafil; 20(S)-protopanaxadiol, oleanolic acid ( Lin et al, 2021 ), which is an active compound found in ginseng and a Chinese herb gastrodin ( Wang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies using natural compounds showed an overall positive effect ( Yang et al, 2013 ; SoukhakLari et al, 2018 ; Tang et al, 2018 ; Ahmad Rather et al, 2019 ; Huang et al, 2019 ; Li et al, 2019 ; Yao et al, 2019 ; Jiang et al, 2020 ; Chou and Yang, 2021 ; Ren et al, 2021 ; Saleh et al, 2021 ; Wang et al, 2021 ; Yan et al, 2021 ) on cognition, seven studies a moderately positive ( Madhavadas and Subramanian, 2017 ; Yan et al, 2017 ; Wang et al, 2018 ; Liao et al, 2019 ; Zhu et al, 2019 ; Sun et al, 2020 ; Lin et al, 2021 ) and one a negative effect ( Jiang et al, 2020 ). The effect of natural compounds on cognition were tested in dementia animal models in rat ( n = 7 out of 21 studies); mice ( n = 14 out of 21 studies), and in normal ageing animal model in mice [ n = 1 out of 1 study ( Jiang et al, 2020 )].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, FOXO1 was found to be targeted by miR-27a-3p. FOXO1 upregulation could inhibit the cell growth [ 11 ], while Grb2 can promote the cell proliferation [ 29 ]. Thus, the different function between FOXO1 and Grb2 might result in this discrepancy.…”
Section: Discussionmentioning
confidence: 99%